2000
DOI: 10.1002/hep.510310211
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of hepatocellular carcinoma increases the chance of treatment: Hong Kong experience

Abstract: The prognosis for patients with hepatocellular carcinoma (HCC) is poor because of the low chance of curative treatment. To increase the chance of intervention and to improve survival, early detection of subclinical HCC (SCHCC) by ␣-fetoprotein (AFP) and/or ultrasonography (USG) screening is implemented in many countries. Three hundred six Chinese patients with HCC diagnosed between January 1995 and December 1997 were recruited. They were categorized into two groups: 142 patients (group 1) had SCHCC diagnosed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
269
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(293 citation statements)
references
References 25 publications
16
269
2
6
Order By: Relevance
“…This is consistent with the results of Yuen et al [19], who found that patients in who HCC was diagnosed by screening had a lower median a-FP level (111 vs. 825.5 ng/mL), smaller mean size of solitary lesions (3.7 ± 2.4 vs. 5.8 ± 3.5 cm), and lesser chance of bilobar involvement, diffuse HCC, PVT, and metastasis among screened patients versus unscreened patients, respectively. Similarly, Farinati and Gianni [20], in a study of 280 Italian patients, showed that patients in whom HCC was diagnosed by screening had an earlier tumor staging than unscreened patients, resulting in a mean gain in survival of 16 months even after adding 10 months to the survival for the unscreened patients.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with the results of Yuen et al [19], who found that patients in who HCC was diagnosed by screening had a lower median a-FP level (111 vs. 825.5 ng/mL), smaller mean size of solitary lesions (3.7 ± 2.4 vs. 5.8 ± 3.5 cm), and lesser chance of bilobar involvement, diffuse HCC, PVT, and metastasis among screened patients versus unscreened patients, respectively. Similarly, Farinati and Gianni [20], in a study of 280 Italian patients, showed that patients in whom HCC was diagnosed by screening had an earlier tumor staging than unscreened patients, resulting in a mean gain in survival of 16 months even after adding 10 months to the survival for the unscreened patients.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with several previous studies exploring evolutionary temporal trends in HCC. The role of HCC surveillance in chronic liver disease has become well established over the years, with benefits reported in several studies 42, 43, 44. Similarly, a significant improvement in diagnostic modalities, such as dynamic computerized tomography, contrast‐enhanced magnetic resonance imaging, and ultrasound, has also played an important role in detecting HCC earlier 35.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance for HCC is now a part of standard clinical practice for patients with chronic viral hepatitis [8]. Considering recent advances in HCC treatments, surveillance is required to detect HCC while tumors are small enough for the indication of curative treatments such as surgical resection and radiofrequency ablation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%